Estructuración de un modelo de una planta de producción y comercialización de alimentos balanceados para la industria avícola en la provincia de Santo Domingo de los Tsachilas - Cabrera Jaramillo, Norge Antonio (2008)
This project is in response to that there are few industries that do not cover the total demand, so that unmet demand is supplied by neighboring industries to the province of Santo Domingo de los Tsachilas and mainly the province of Guayas.